An in silico hiPSC-Derived Cardiomyocyte Model Built With Genetic Algorithm - Akwaboah, Akwasi D.; Tsevi, Bright; Yamlome, Pascal; Treat, Jacqueline A.; Brucal-Hallare, Maila; Cordeiro, Jonathan M.; Deo, Makarand (Frontiers in Physiology, 2021)
The formulation of in silico biophysical models generally require optimization strategies for reproducing experimentally observed phenomena. In electrophysiological modeling, robust nonlinear regressive methods are often crucial for guaranteeing high fidelity models. Human induced pluripotent stem cell-derived cardiomyocytes (hiPSC-CMs), though nascent, have proven useful in cardiac safety pharmacology, regenerative medicine, and in the implementation of patient-specific test benches for investigating inherited cardiac disorders. This study demonstrates the potency of heuristic techniques at formulating biophysical models, with emphasis on a hiPSC-CM model using a novel genetic algorithm (GA) recipe we propose. The proposed GA protocol was used to develop a hiPSC-CM biophysical computer model by fitting mathematical formulations to experimental data for five ionic currents recorded in hiPSC-CMs. The maximum conductances of the remaining ionic channels were scaled based on recommendations from literature to accurately reproduce the experimentally observed hiPSC-CM action potential metrics. Near-optimal parameter fitting was achieved for the GA-fitted ionic currents. The resulting model recapitulated experimental action potential parameters such as action potential durations (APD50, APD75, and APD90), maximum diastolic potential and frequency of automaticity. The outcome of this work has implications for validating the biophysics of hiPSC-CMs in their use as viable substitutes for human cardiomyocytes, particularly in cardiac safety pharmacology and in the study of inherited cardiac disorders. This study presents a novel GA protocol useful at formulating robust numerical biophysical models. The proposed protocol is used to develop an hiPSC-CM model with implications for cardiac safety pharmacology.